Sistem Pendukung Keputusan Pemilihan Merek Body Lotion Lokal Terbaik untuk Mencerahkan Kulit dengan Menggunakan Metode MAUT - Nurul Aisyah; Selly Andari; Ririn Nadya Utari; Nadya; Dedy Hartama; Putrama Alkhairi (Journal of Computing and Informatics Research, 2026)
This study aims to determine the best local body lotion brand for skin brightening using the Multi-Attribute Utility Theory (MAUT) method. MAUT was chosen for its capability to process data based on various criteria such as benefits, quality, effectiveness, price, and brand reputation. Data were collected through online questionnaires distributed via Google Forms and shared on social media. From 36 alternatives, five local brands were selected for analysis: Marina, Citra, Scarlett, Natur-e, and Herborist. The analysis process involved determining the weight of each criterion, matrix normalization, utility evaluation, and alternative ranking. The results indicate that Marina ranks first with a score of 19, followed by Scarlett (8.7) and Citra (8.1). The MAUT method has proven effective in supporting decisions regarding the selection of the best local body lotion brand, providing objective and structured guidance for consumers.